2019
DOI: 10.1108/ils-06-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

The building blocks of coding: a comparison of early childhood coding toys

Abstract: Purpose This paper aims to be a think piece that promotes discussion around the design of coding toys for children. In particular, the authors examine three different toys that have some sort of block-based coding interface. The authors juxtapose three different design features and the demands they place on young children learning to code. To examine the toys, the authors apply a framework developed based on Gibson’s theory of affordances and Palmer’s external representations. The authors look specifically at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…This study, similar to Clarke-Midura et al's (2019) study, makes no claims about whether one coding app is superior to another, as these apps all originate from high-quality methodological research on educational technology. However, the results presented in this study should serve as a benchmark and challenge for teachers, researchers, and software developers to be mindful of what demands and expectations we are placing on young children as they learn to code (Clarke-Midura et al, 2019). Indeed, the findings showed that the essential CT and coding skills mentioned in known CT frameworks could be delivered using the four different apps mentioned in this study.…”
Section: Discussion and Future Directionsmentioning
confidence: 79%
See 4 more Smart Citations
“…This study, similar to Clarke-Midura et al's (2019) study, makes no claims about whether one coding app is superior to another, as these apps all originate from high-quality methodological research on educational technology. However, the results presented in this study should serve as a benchmark and challenge for teachers, researchers, and software developers to be mindful of what demands and expectations we are placing on young children as they learn to code (Clarke-Midura et al, 2019). Indeed, the findings showed that the essential CT and coding skills mentioned in known CT frameworks could be delivered using the four different apps mentioned in this study.…”
Section: Discussion and Future Directionsmentioning
confidence: 79%
“…Some children may struggle with what to do or why to edit sprites or build animations. As Clarke-Midura et al (2019) highlight, some children may not be able to afford to support coding independently, and apps like ScratchJr may require special attention, scaffolding, and systematic instruction in real educational settings. Thus, one could conclude that it could be more beneficial for children some structure or narrative to help them learn some concepts in the initial stages of coding.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations